2022
DOI: 10.3389/fonc.2022.936952
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the prognostic value and immune infiltration of FGFR family members in gastric cancer

Abstract: BackgroundFibroblast growth factor receptors (FGFRs) modulate numerous cellular processes in tumor cells and tumor microenvironment. However, the effect of FGFRs on tumor prognosis and tumor-infiltrating lymphocytes in gastric cancer (GC) remains controversial.MethodsThe expression of four different types of FGFRs was analyzed via GEPIA, TCGA-STAD, and GTEX databases and our 27 pairs of GC tumor samples and the adjacent normal tissue. Furthermore, the Kaplan–Meier plot and the TCGA database were utilized to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Immunotherapy such as anti-PDL1 therapy has been shown to have more effect in FGFR wild-type tumors in bladder cancer cell lines while less effects from immunotherapy were observed in FGFR4-overexpressed gastric cancer cells [144,145]. Patients with FGFR1overexpressed melanoma were also found to have less response to pembrolizumab while FGFR-altered HCC tends to have progressive disease after immunotherapy [146][147][148].…”
Section: Future Therapeutic Combinations With Fgf/fgfr Inhibitorsmentioning
confidence: 99%
“…Immunotherapy such as anti-PDL1 therapy has been shown to have more effect in FGFR wild-type tumors in bladder cancer cell lines while less effects from immunotherapy were observed in FGFR4-overexpressed gastric cancer cells [144,145]. Patients with FGFR1overexpressed melanoma were also found to have less response to pembrolizumab while FGFR-altered HCC tends to have progressive disease after immunotherapy [146][147][148].…”
Section: Future Therapeutic Combinations With Fgf/fgfr Inhibitorsmentioning
confidence: 99%
“…This is associated not only with T-cell exhaustion due to increased PD-1 expression, but also with decreased clonality and infiltration. FGFR4 expression is negatively correlated with the number of infiltrating lymphocytes in gastric malignancies [ 54 ]. FGFR3 -mutant urothelial carcinomas have also been noted to possess an immune microenvironment background with increased T-cell exhaustion [ 55 ].…”
Section: Fgf/fgfr Signaling and Tmementioning
confidence: 99%
“…This FGFR signaling promotes interleukin (IL)-2 production by degrading IκBα and activating NF-κB, which promotes T-lymphocyte proliferation by activating RAS and PI3K with the help of SNT-like proteins [ 71 , 72 ]. Bioinformatic analysis of tissues from gastric cancer patients also revealed that the degree of infiltration of CD8 + and CD4 + T-cells, macrophages and DCs was positively correlated with the expression of FGFR1 in tumor cells [ 54 ]. This suggests that the mechanisms by which different FGFR activating alterations act in tumors may be different and regulated by different factors and require more detailed and comprehensive studies for elucidation.…”
Section: Fgf/fgfr Signaling and Tmementioning
confidence: 99%
See 2 more Smart Citations